Corn cob valorization: Synthesis of a polymer based on crystalline cellulose with poly(ethylene glycol) diacrylate and N-vinylcaprolactam - Paola Gutiérrez; Miguel Aldas; Dayana Gavilanes; Francisco Cadena; Vladimir Valle (Cleaner Engineering and Technology)
A growing trend in research is the use of agro-industrial waste as a renewable raw material. Cellulose is among the most abundant and versatile biopolymers, which can be derived from agro-industrial waste like corn cobs. This study explored the valorization of corn cob (CM) waste through the extraction of crystalline cellulose (CC) and its modification via radical emulsion polymerization with poly (ethylene glycol) diacrylate (PEGDA) and N-vinylcaprolactam (N-VCL). CC was extracted from CM through pulping, bleaching, and acid hydrolysis, achieving a yield of 67 %. Characterization by scanning electron microscopy (SEM) revealed a fibrillary structure with sizes below 100 μm. X-ray diffraction (XRD) demonstrated a crystallinity index of 98.72 % and characteristic peaks of type I cellulose. Fourier-transform infrared spectroscopy (FTIR) confirmed the removal of hemicellulose, lignin, and amorphous cellulose. Thermal Gravimetric Analysis (TGA) indicated thermal stability up to 369 °C. In the grafted copolymer CC-g-poly (PEGDA-co-N-VCL), with a polymerization yield of 83.91 %, FTIR confirmed the incorporation of PEGDA and N-VCL. SEM analysis revealed a homogeneous three-dimensional surface without visible fibrils, indicating successful grafting. Differential Scanning Calorimetry (DSC) analyses showed transitions at 340 °C, 427 °C, and 460 °C, reflecting enhanced thermal stability, while TGA revealed less gradual degradation in the copolymer, with mass loss stages at higher temperatures. This grafted material exhibited improved thermal stability and lower water absorption than the unmodified CC, highlighting its potential for applications requiring high thermal resistance and moisture control.